2004
DOI: 10.1128/jvi.78.20.11379-11384.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Apoptosis of Peripheral CD5-Negative B Lymphocytes from Chronically Hepatitis C Virus-Infected Patients: Reversal after Antiviral Treatment

Abstract: Whereas enhanced peripheral T-cell apoptosis and its association with autoimmunity have recently been reported, the apoptotic status of peripheral B cells in chronic hepatitis C virus (HCV) infection remains ambiguous. We therefore sought to investigate the sensitivity of peripheral B cells to apoptosis and to assess the possible benefits of antiviral treatment in mitigating these effects. Spontaneous apoptosis, the extent of apoptosis rescue, and NF-B expression in peripheral B cells were studied in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…However, it should be pointed out that the level of apoptosis correlated inversely with HCV RNA load in serum Furthermore, the dynamics of CD19+ B cells were reverse, as patients with double infection had higher apoptosis than HIV-monoinfected patients, and apoptosis decreased during antiviral treatment. The latter findings are compatible with those reported by Toubi et al, who found that spontaneous B cell apoptosis is increased in chronic hepatitis C but returns to normal values in sustained responders to antiviral treatment [23]. …”
Section: Discussionsupporting
confidence: 92%
“…However, it should be pointed out that the level of apoptosis correlated inversely with HCV RNA load in serum Furthermore, the dynamics of CD19+ B cells were reverse, as patients with double infection had higher apoptosis than HIV-monoinfected patients, and apoptosis decreased during antiviral treatment. The latter findings are compatible with those reported by Toubi et al, who found that spontaneous B cell apoptosis is increased in chronic hepatitis C but returns to normal values in sustained responders to antiviral treatment [23]. …”
Section: Discussionsupporting
confidence: 92%
“…The presence of anti-CRP might disturb this process, thus increasing the exposure of autoantigens to the immune system and thereby promoting the development of autoantibodies. Specifically in the case of HCV infection, increased apoptosis of T and B (CD19 ϩ CD5 Ϫ ) lymphocytes in the presence of anti-CRP may prolong exposure of the nuclear antigens to (CD19 ϩ CD5 ϩ ) B lymphocytes and thereby increase the possibility of autoantibody formation, consistent with the finding of the present study [26,27]. It should be emphasized that anti-CRP antibodies are directed against the monomeric (modified) form of CRP, i.e., epitopes that are hidden in the pentameric structure of CRP.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard we have recently shown that in patients with chronic HCV infection, CD5þ B cells were found resistant to the induction of spontaneous apoptosis [30], which may link this finding with the detected elevation of serum BAFF in these patients. Over-production of BAFF in chronic HCV infection may attenuate the sensitivity of B cells to undergo spontaneous apoptosis thus prolonging their survival.…”
Section: Discussionmentioning
confidence: 83%